Miasthenia gravis in pediatric age - Liubka María Pérez Mederos; María Ofelia Hernández Oliver; Cecilio González Benavides; José Manuel González Santos (Acta Médica del Centro, 2008)
Background: Myasthenia gravis is an autoimmune disorder characterized by fluctuating muscle weakness and fatigue of different muscle groups, secondary to a synaptic transmission alteration caused by the blockade and destruction of the acetylcholine receptors in the neuromuscular junction. Objective: To establish the main features of myasthenia gravis in the Paediatric Hospital “Jose Luis Miranda” of Villa Clara during the last ten years. Methods: It was made a review of 5 clinical histories of patients diagnosed with myasthenia gravis in the above mentioned medical institution. Results: Our study includes five patients with the diagnosis of myasthenia gravis. Three of them had a generalized onset and the rest had an ocular onset. The diagnosis was made at very different ages from four to sixteen years old. Three children had thymus hyperplasia and two of them received surgical treatment after they were 9 years, nevertheless both of them had to continue with inmunosupressor treatment. The less successful case was the patient with the ocular myasthenia, which was the youngest one. Conclusions: We consider that thymectomy should be indicated in children with generalized immunological myasthenia which do not improves with steroids or with ganmaglobulins. Thymectomy should be avoided in very young people avoiding this way the risk of immunodeficiency.